Audit committee characteristics and net margin: empirical evidence from listed land and property companies in sri lanka - Kevin, T.J.; Mithushana, R. (University of Jaffna, 2019)
The purpose of this paper is to examine the impact of audit committee characteristics on the net margin of Land and Property Companies in Sri Lanka.The population of the study comprises firms listed under Land and Property sector in Colombo Stock Exchange. The number of firms listed underLandand Property sector in Colombo Stock Exchange as at the time of data collection (2018) was 19, out of which 10 were used as sample for this study. The data were collected for the period from 2012 to 2018 and obtained from the web site of Colombo Stock Exchange. Audit committee members and audit committee independence are considered as independent variables of study. The dependent variable was net margin of the firm which obtained directly through the annual reports of the companies. In addition to this board meetings, company age, board size were considered as control variables in this study. To test the hypothesis of this study, simple least square regression was utilized by using EViews 8 version. The findings suggest a significant positive relationship between audit committee members, company age, board size and net margin. Also there is a significant negative relationship between auditor independence and net margin. Board meeting shows an insignificant relationship with the net margin. Due to lack of researches covering this areas in Sri Lankan Land and Property sector, this study would provide additional knowledge to future researchers and academicians.
Keywords: Corporate governance; Audit committee; Net margin; Land and property; Colombo stock exchange